Optimum time for collecting root samples for chromosome observation in Dioscorea spp. - Babil, P.K.; Kikuno, H.; Shiwachi, H.; Toyohara, H.; Fujigaki, J.; Fujimaki, H.; Asiedu, Robert (2010)
The genus Dioscorea is considered to be one of the most difficult groups for cyto-taxonomic studies because of the large number and small size of the chromosomes. The objective of the present study was to develop an efficient method of chromosome. Observation by identifying the optimum time for collecting root samples containing large number so for metaphase cells. In the present investigation, two breeders’ lines developed at IITA, TDa98/01183(D. alata) and TDr95/18544(D. rotundata) which were identified as tetraploids (2n=4x=40) were used. To take samples for observation, root tips were collected from vine cutting sand seed tuber sets. In the root cells obtained from the seed Tuber sets of both cultivars, TDa18544, two peaked in the frequency of metaphase cells appeared in the diurnal cycle of cell division. The first peak was observed at seven hours after sunrise (1:00pm) and the second at19hours after sunrise (1:00am). In the roots of the seedlings obtained from vine cuttings thirst peak of frequency of metaphase cells appeared at four hours after sunrise (10:00am) in both cultivar sand the second peak at 16hours (10:00pm) in TDa98/01183, but at 13hours in TDr9n the results obtained, a cycle of cell division is considered to exhibit a periodicity of about 12hours. The present investigation enabled to identify the optimum times for collecting root tips samples from rooted vine cuttings and seed tuber sets. The findings may facilitate cytogenetic studies in yams.